2022
DOI: 10.1136/bmjopen-2021-052185
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ views on volunteering in mental health: an international focus group study

Abstract: ObjectivesExplore the views of two main stakeholders: mental health professionals and volunteers from three European countries, on the provision of volunteering in mental healthcare.DesignA multicountry, multilingual and multicultural qualitative focus group study (n=24) with n=119 participants.ParticipantsVolunteers and mental health professionals in three European countries (Belgium, Portugal and the UK).ResultsMental health professionals and volunteers consider it beneficial offering volunteering to their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 15 It plays a pivotal role in public health promotion and constitutes a key component of clinical governance. 16 Volunteering also improves patient satisfaction, fosters trust, reduces anxiety and negative emotions, 17 reduces the adverse physical and mental effects of crises and facilitates disease management. 18 Despite its positive effects, voluntary care provision is associated with challenges and concerns.…”
Section: Introductionmentioning
confidence: 99%
“… 15 It plays a pivotal role in public health promotion and constitutes a key component of clinical governance. 16 Volunteering also improves patient satisfaction, fosters trust, reduces anxiety and negative emotions, 17 reduces the adverse physical and mental effects of crises and facilitates disease management. 18 Despite its positive effects, voluntary care provision is associated with challenges and concerns.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that volunteer engagement in stroke programs strengthens intervention delivery by ensuring that important health messages are effectively disseminated to clients. Through the use of lay language, volunteers, particularly those from the general public, enhance the immediate applicability of delivered health information for clients and minimize barriers in understanding that may arise from professional distance between healthcare professionals and clients [ 15 , 16 ]. Moreover, previous evidence has highlighted the benefits of participation for the volunteers themselves, who have reported enhanced learning, understanding and empathy after interacting with clients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%